Notification-Based Inventory System in the Security Industry : A Systematic Literature Review - Kalaichelvan, Malven; Mohd Taha, Nor Fyadzillah (Semarak International Journal of Transportation and Logistics, 2025)
This systematic literature review investigates the effectiveness of notification-based inventory systems in the security industry, with KR META Security as a focal case. Despite advances in digital transformation, many firms continue to rely on manual tracking methods, creating risks of inaccuracy, delay, and asset misplacement. Using the PRISMA 2020 approach, 90 records were initially identified, and after screening and eligibility checks, 15 studies were included for final synthesis. The review revealed major barriers to adoption, including high cost, technical complexity, cybersecurity risks, and organizational resistance. Conversely, enablers such as government digitalization support, cloud scalability, and real-time alert mechanisms were highlighted as critical success factors. Compared with other industries, the security sector faces greater urgency due to the mission-critical nature of its assets, where inventory lapses can directly compromise operational readiness. To bridge these gaps, a three-layer conceptual framework comprising technological, operational, and management dimensions is proposed to improve inventory visibility, strengthen asset control, and accelerate incident response. This framework provides a tailored pathway for security firms to transition from manual practices to secure, efficient, and reliable notification-based systems.